Structural analysis of calcium reactive hydride composite for solid state hydrogen storage. (4th February 2014) - Karimi, Fahim; Pranzas, P. Klaus; Hoell, Armin; Vainio, Ulla; Welter, Edmund; Raghuwanshi, Vikram S.; Pistidda, Claudio; Dornheim, Martin; Klassen, Thomas; Schreyer, Andreas
<x xml:space="preserve">Abstract</x> Owing to a theoretical hydrogen storage capacity of 10.5 wt% H2, Ca(BH4)2+MgH2, the so‐called calcium reactive hydride composite (Ca‐RHC), has a great potential as a hydrogen storage material. However, its dehydrogenation temperature (∼623 K) is too high for any mobile applications. By addition of 10 mol% of NbF5 into Ca(BH4)2+MgH2, a decrease of the dehydrogenation onset temperature by ∼120 K is observed. In order to understand the reasons behind this desorption temperature decrement two sets of samples [Ca(BH4)2+MgH2 and Ca(BH4)2+MgH2+0.1NbF5] in different hydrogenation states, were prepared. The structural investigation of the above mentioned sets of samples by means of volumetric measurements, anomalous small‐angle X‐ray scattering (ASAXS) and X‐ray absorption spectroscopy (XAS) is reported here. The XAS results show that after the milling procedure NbB2 is formed and remains stable upon further de/rehydrogenation cycling. The results of Nb ASAXS point to nanometric spherical NbB2 particles distributed in the hydride matrix, with a mean diameter of ∼10 nm. Results from Ca ASAXS indicate Ca‐containing nanostructures in the Ca‐RHC+0.1NbF5 samples to be ∼50% finer compared to those without additive. Thus, a higher reaction surface area and shorter diffusion paths for the constituents are concluded to be important contributions to the catalytic effect of an NbF5 additive on the hydrogen sorption kinetics of the Ca(BH4)2+MgH2 composite system.